The bilingual family a handbook for parents - Esch, Edith 1945- (Cambridge University Press, 2003)
First published in 1986, The Bilingual Family has provided thousands of parents with the information and advice they need to make informed decisions about what language policy to adopt with their children. This second edition contains updated references and new entries to the alphabetical reference guide